Multidimensional Framework for the Analysis of Innovations at Universities in Catalonia - TOMAS, Marina; CASTRO, Diego (Education Policy Analysis Archives, 2011)
The purpose of this paper is to contribute to a better understanding of the nature of change processes and dynamics at Catalan universities. A multidimensional approach was adopted to examine the change processes and to analyse organizational innovation in higher education. The paper draws involved in each particular innovation. Analysis of these innovations has led to the identification of common characteristics and a proposal for a multidimensional framework for future innovation analysis. Finally, the innovation cases analysed highlighted interactions between three innovation characteristics, defined as scope (number of people involved), nature (organizational or curricular) and term (short, medium or long).